The Effect of Transformational Leadership and Work Motivation on Employee Performance: Job Satisfaction as Mediation - Mariyatha, I Made (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
The success of an organisation depends on its human resources, including government agencies, so that human resource management is needed to support employee performance. This study aims to determine and explain the effect of transformational leadership and work motivation on employee performance through job satisfaction. This research uses a quantitative approach. The research location is the Bali Province Language Centre. The population used all employees at the Bali Province Language Centre while the sample size was determined using purposive sampling of 40 respondents. The data collection method used is a survey method with a questionnaire. The analysis technique is inferential technique with Partial Least Square (PLS). The results concluded that transformational leadership has no significant effect on performance but has a significant positive effect on job satisfaction. Work motivation has no significant effect on performance but has a significant positive effect on job satisfaction. Job satisfaction has a significant positive effect on employee performance. Job satisfaction fully mediates the effect of transformational leadership on employee performance. Job satisfaction partially mediates the effect of work motivation on employee performance.